2009
DOI: 10.1038/ng.370
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant ERG expression cooperates with loss of PTEN to promote cancer progression in the prostate

Abstract: Chromosomal translocations involving the ERG locus are frequent events observed in human prostate cancer pathogenesis, however the biologic role of ERG aberrant expression is controversial. 1 Here we demonstrate that the aberrant expression of ERG is a progression event in prostate tumorigenesis. We find that prostate cancer specimens containing the TMPRSS2:ERG genetic rearrangement are significantly enriched for loss of the tumor suppressor PTEN. In concordance with these findings, over-expression of ERG in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

40
568
6
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 600 publications
(627 citation statements)
references
References 25 publications
40
568
6
4
Order By: Relevance
“…They further analyzed tumor samples demonstrating that 68% (27/ 40) of prostate cancers had loss of PTEN expression by immunohistochemistry in contrast to 38% (15/40) of cases with ERG rearrangement. 47 50 confirmed that these finding demonstrate that the overexpression of ERG is associated with tumor cell migration through a proteolytic molecular program. Recently, Carver et al 47 performed a series of studies to explore the concomitant relationship between TMRPSS2:ERG and the pten/PI3K/Akt pathways.…”
Section: A Multitude Of Gene Fusions In Prostate Cancersupporting
confidence: 73%
See 2 more Smart Citations
“…They further analyzed tumor samples demonstrating that 68% (27/ 40) of prostate cancers had loss of PTEN expression by immunohistochemistry in contrast to 38% (15/40) of cases with ERG rearrangement. 47 50 confirmed that these finding demonstrate that the overexpression of ERG is associated with tumor cell migration through a proteolytic molecular program. Recently, Carver et al 47 performed a series of studies to explore the concomitant relationship between TMRPSS2:ERG and the pten/PI3K/Akt pathways.…”
Section: A Multitude Of Gene Fusions In Prostate Cancersupporting
confidence: 73%
“…47 50 confirmed that these finding demonstrate that the overexpression of ERG is associated with tumor cell migration through a proteolytic molecular program. Recently, Carver et al 47 performed a series of studies to explore the concomitant relationship between TMRPSS2:ERG and the pten/PI3K/Akt pathways. Benign prostate cells (BPH-1) demonstrate increased proliferation with constitutively overexpressed Akt (AKT-1) as compared to controls.…”
Section: A Multitude Of Gene Fusions In Prostate Cancersupporting
confidence: 73%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Most commonly, fusion of the transcriptional regulator gene ERG (ETSrelated gene) with TMPRSS2 is seen, present in half or more of prostate cancers, although other partner genes, such as ETV1, ETV4 and ETV5, may be involved in translocations. 1,2,7 Subsequent studies have found these gene fusions to appear early in prostate cancer development, 6 present in a subset of cases of prostatic intra-epithelial neoplasia and putative precursor lesions.…”
mentioning
confidence: 99%
“…However, other genetic alterations appear to be contributory components of tumor development, such as loss of PTEN and activation of the PI3-kinase pathway, particularly in the setting of progression from an intraepithelial neoplasm to invasive adenocarcinoma. 2,4,12 Although abnormalities of ETS genes are sometimes found in tumors of other organs, ERG-TMPRSS2 fusion is not seen in common neoplasms of other sites, both epithelial and non-epithelial. 3 As such, these abnormalities have begun to demonstrate tremendous potential for broad applications in diagnosis, prognostication and treatment of prostate cancer.…”
mentioning
confidence: 99%